2018
DOI: 10.1038/s41598-018-29715-w
|View full text |Cite
|
Sign up to set email alerts
|

Rice Defensin OsAFP1 is a New Drug Candidate against Human Pathogenic Fungi

Abstract: Fungal infections, such as candidiasis and aspergillosis, are some of the most frequent infections in humans. Although antifungal drugs are available for the treatment of these infections, antifungal agents with new mechanisms of action should be developed because of the increasing incidence of drug-resistant pathogens in recent years. In this study, a basic functional analysis of rice defensin OsAFP1, a novel antifungal drug candidate, was conducted. OsAFP1 exerted fungicidal activity against Candida albicans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 56 publications
(58 reference statements)
1
27
0
1
Order By: Relevance
“…The following defensins of rice Oryza sativa L. were studied in detail: OsDEF7 and OsDEF8 by Tantong et al [ 67 ] and Weerawanich et al [ 93 ]; OsDEF7, named OsAFP1, was further studied by Sagehashi et al [ 94 ] and Ochiai et al [ 95 ], while Cal1, identical to OsDEF7, was analyzed by Luo et al [ 96 ].…”
Section: Defensins Of Grassesmentioning
confidence: 99%
See 4 more Smart Citations
“…The following defensins of rice Oryza sativa L. were studied in detail: OsDEF7 and OsDEF8 by Tantong et al [ 67 ] and Weerawanich et al [ 93 ]; OsDEF7, named OsAFP1, was further studied by Sagehashi et al [ 94 ] and Ochiai et al [ 95 ], while Cal1, identical to OsDEF7, was analyzed by Luo et al [ 96 ].…”
Section: Defensins Of Grassesmentioning
confidence: 99%
“…Ochiai et al [ 95 ] studied the effect of OsDEF7 on the growth of human pathogenic fungi and showed that the peptide exerted fungicidal activity against Candida albicans at a concentration of 22.2 µg/mL. The recombinant peptide also inhibited the growth of two Saccharomyces cerevisiae strains (MIC = 22.2 µg/mL and 88.8 µg/mL), but failed to inhibit the growth of human pathogenic bacteria, such as Gram-negative bacteria E. coli K-12 and Porphyromonas gingivalis , and Gram-positive bacteria Streptococcus mutans , Staphylococcus aureus , and Propionibacterium acnes at concentrations below 177.7 µg/mL.…”
Section: Defensins Of Grassesmentioning
confidence: 99%
See 3 more Smart Citations